Perbedaan Tingkat Self Control pada Mahasiswa Bimbingan dan Konseling Universitas Sanata Dharma Pengguna Media Sosial X (Twitter) ditinjau dari Jenis Kelamin - Alda Veniza Dewi; Bernardinus Agus Arswimba (Universitas Palan, 2024)
This research aims to (1) Knowing the differences in self-control among guidance and counseling students at Sanata Dharma University who use social media X (Twitter) based on gender. (2) Determine the level of self-control among guidance and counseling students at Sanata Dharma University who use social media X (Twitter). (3) Knowing the level of self-control among guidance and counseling students at Sanata Dharma University who use social media X (Twitter). Type of quantitative research with a comparative approach. The subjects in this research were BK USD students who used Twitter, totaling 30 male and 30 female students. The questionnaire is based on Averill's self-control theory (in Ghufron and Risnawati, 2010) which has three aspects including: Behavioral control, cognitive control, and control in making decisions. The validity test results obtained a total of 39 valid items.The research results show differences in the level of self-control between guidance and counseling male students and female students who use social media based on the results of Mann Whitney, asymp. the significant value is 0.000 < 0.05, then the Ha (alternative hypothesis) is accepted and the Ho (null hypothesis) is rejected. Male students have lower self-control than female students. Male students tend to have a moderate level of self-control around 21 (70%) and female students tend to have a high level of self-control around 21 (70%).